Primary and Secondary Organic Marine Aerosol and Oceanic Biological Activity: Recent Results and New Perspectives for Future Studies. (16th May 2010) - Rinaldi, Matteo; Decesari, Stefano; Finessi, Emanuela; Giulianelli, Lara; Carbone, Claudio; Fuzzi, Sandro; O'Dowd, Colin D.; Ceburnis, Darius; Facchini, Maria Cristina
Abstract : One of the most important natural aerosol systems at the global level is marine aerosol that comprises both organic and inorganic components of primary and secondary origin. The present paper reviews some new results on primary and secondary organic marine aerosol, achieved during the EU project MAP (Marine Aerosol Production), comparing them with those reported in the recent literature. Marine aerosol samples collected at the coastal site of Mace Head, Ireland, show a chemical composition trend that is influenced by the oceanic biological activity cycle, in agreement with other observations. Laboratory experiments show that sea-spray aerosol from biologically active sea water can be highly enriched in organics, and the authors highlight the need for further studies on the atmospheric fate of such primary organics. With regard to the secondary fraction of organic aerosol, the average chemical composition and molecular tracer (methanesulfonic-acid, amines) distribution could be successfully characterized by adopting a multitechnique analytical approach.